2020
DOI: 10.1520/jte20180856
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Surface Morphology and Topography Features on Abrasive Water Jet Milled Surface Pattern of SS 304

Abstract: Among the nontraditional milling processes, abrasive water jet (AWJ) is a cold machining technique for producing surface textures on a wide variety of materials. This article reports the feasibility study of producing biomedical implant surface pattern on stainless steel 304 using controlled deposition of AWJ milling. Preliminary investigation on the AWJ-milled surface pattern was carried out through the controllable milling parameters such as fluid pressure, stand-off distance (SOD), nozzle feed rate and garn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Overview articles [ 1 , 2 ] provide a comprehensive review of the AWJ process parameters. Some researchers even try to control the surface texture with process parameters [ 3 ]. Many traditional modeling techniques, such as regression analysis, do not provide satisfactory results, especially when the relationship between the target function and the influencing parameters is non-linear, as is usually the case in complex phenomena (such as AWJ machining); this indicates the appropriateness of artificial neural network (ANN) based methods for overall cutting process modeling [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overview articles [ 1 , 2 ] provide a comprehensive review of the AWJ process parameters. Some researchers even try to control the surface texture with process parameters [ 3 ]. Many traditional modeling techniques, such as regression analysis, do not provide satisfactory results, especially when the relationship between the target function and the influencing parameters is non-linear, as is usually the case in complex phenomena (such as AWJ machining); this indicates the appropriateness of artificial neural network (ANN) based methods for overall cutting process modeling [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bannerji et al [8] have reported poor corrosion performance of LSP ZE41 Mg which has no Al content, indicating the importance of Aluminium presence in Mg alloy [9]. However, AZ31B Mg alloys show rapid and intense corrosion rate in physiological environment [10] leading to adverse effects and harm to tissues during recovery. Enhancement of surface texture is mandatory for the inhibition of corrosion characteristics and for the achievement of better osteoblast with natural bones.…”
Section: Introductionmentioning
confidence: 99%
“…The technology of Abrasive waterjet (AWJ) has been widely used in many areas of human activity for several decades. The physical principle of the process is the transfer of mechanical energy from the pump to material and its use for required operations, namely various types of material disintegration such as milling [1,2], machining of composites [3], rock breaking [4], wood cutting [5], and many others. One of the most frequent and important applications of this technology is material cutting.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most frequent and important applications of this technology is material cutting. Its efficiency should be evaluated from two points of view: either by the amount of consumed energy along with the costs, or by the evaluation of the quality of the cut, namely the surface roughness and cutting accuracy [2,[5][6][7][8]. In the case of plain dividing cuts, the quality is usually not the most important thing.…”
Section: Introductionmentioning
confidence: 99%